2006
DOI: 10.1007/s11746-006-1213-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids, tocols, and carotenoids in pulp oil of three sea buckthorn species (Hippophae rhamnoides, H. salicifolia, and H. tibetana) grown in the Indian Himalayas

Abstract: Sea buckthorn berries from Hippophae rhamnoides, H. tibetana, and H. salicifolia were collected from the cold deserts of the Himalayas (Lahaul, Ladakh, and Spiti; India) and characterized in terms of the FA, carotenoid, tocopherol, and tocotrienol composition in their pulp oil. These varied from species to species. Total carotenoids ranged from 692 to 3420 mg/kg in pulp oils of fresh berries, and total tocols, from 666 to 1788 mg/kg. Hippophae salicifolia berries contained substantially lower amounts of pulp o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 18 publications
5
67
0
Order By: Relevance
“…Total amounts of carotenoids were determined using Ranjith et al (2006) following some modifications. GSO were dissolved in hexane (0.1 g mL -1…”
Section: Total Carotenoidsmentioning
confidence: 99%
“…Total amounts of carotenoids were determined using Ranjith et al (2006) following some modifications. GSO were dissolved in hexane (0.1 g mL -1…”
Section: Total Carotenoidsmentioning
confidence: 99%
“…It is a hardy, deciduous shrub bearing small yellow to orange-red berries and grows widely in Europe, central Asia and the temperate regions of South Asia, India and China. The sea buckthorn berry flour is like a fruit; its seeds and leaves are rich in nutrients and bioactive components such as vitamins, amino acids, lipids, carotenoids, xanthophyll, phenolic and flavonoids and have a higher content of essential oils (Repyakh et al 1990;Bekker & Gluschenkova 1997;Ranjith et al 2006;Singh et al 2006;Yang 2009), making it a very beneficial feed supplement for laying hens. Dumbrava et al (2006) reported that feeding poultry with a meal made from sea buckthorn fruit has been observed to increase the pigmentation of the egg yolk.…”
Section: Introductionmentioning
confidence: 99%
“…Plant height and fruit colour has significant positive correlation with TPC and TAC suggesting interrelationship between morphological and biochemical traits 20 . Ranjith 21 , et al reported fatty acid composition, carotenoids and tocols of pulp oil. The dominating fatty acid are palmitoleic (46 per cent -49 per cent), palmitic, oleic, linoleic and lenolenic acids.…”
Section: Bioactive Contentmentioning
confidence: 99%